Extending Prayer Marks as a Sign of Worsening Chronic Disease - Cangiano, M; Chisti, Mohammod J; Pietroni, Mark AC; Smith, Jonathan H (Journal of Health, Population and Nutrition, 2011)
A 60-year old Muslim man was admitted to the Dhaka Hospital of ICDDR,B with an exacerbation of his chronic obstructive pulmonary disease. Incidental hyperpigmented skin lesions were noticed overlying the dorsum of his ankles, knees, and elbows. Such asymptomatic areas of thickened, lichenified and hyperpigmented skin are called 'prayer marks' and are well-imprinted on the knees, ankles, and forehead. These are secondary to prolonged periods of pressure over bony prominences during prayer. The patient’s wife stated that the appearance of the elbow marks had coincided with an increase in his breathlessness and subsequent use of his elbows to rise from daily prayers. Prayer marks extending to the elbows could be a sign of worsening chronic disease. Key words: Chronic disease; Elbows, Extending; Prayer marks; Bangladesh DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7877 J HEALTH POPUL NUTR 2011 Jun;29(3):290-291